Review Paper on The Research and Development of Corrosion Inhibitors - Wang, Ting; Zhang, Meiling; Yue, Xintong; Su, Xianmin; Zhou, Yongjie; Sheng, Xincheng; Yang, Zhibo; Yang, Jiang (International Journal of Natural Resources and Environmental Studies, 2024)
Corrosion problems are widely found in various industries, and corrosion inhibitors also play an important role in various corrosion environments, especially in oil exploration. However, as China’s oilfield exploitation enters a high water injection period, the mining environment is becoming more and more harsh, and the requirements for oilfield corrosion inhibitors are getting higher and higher. At the same time, various scaling phenomena have emerged one after another in the process of oilfield exploitation. The corrosion and scale inhibitor with good scale inhibition reflects its advantages, and the integration of corrosion and scale inhibition has become a major tendency in the development of corrosion inhibitors. This review introduces different corrosion inhibitors, and focuses on the research on corrosion inhibitors at home and abroad. At the end of the review, it puts forward views on the future development direction of corrosion inhibitors.